Extracellular matrix particle–glycosaminoglycan composite hydrogels for regenerative medicine applications. Issue 1 (26th September 2017) - Beachley, Vince; Ma, Garret; Papadimitriou, Chris; Gibson, Matt; Corvelli, Michael; Elisseeff, Jennifer
Abstract: Tissue extracellular matrix (ECM) is a complex material made up of fibrous proteins and ground substance (glycosaminoglycans, GAGs) that are secreted by cells. ECM contains important biological cues that modulate cell behaviors, and it also serves as a structural scaffold to which cells can adhere. For clinical applications, where immune rejection is a constraint, ECM can be processed using decellularization methods intended to remove cells and donor antigens from tissue or organs, while preserving native biological cues essential for cell growth and differentiation. In this study, a decellularized ECM‐based composite hydrogel was formulated by using modified GAGs that covalently bind tissue particles. These GAG–ECM composite hydrogels combine the advantages of solid decellularized ECM scaffolds and pepsin‐digested ECM hydrogels by facilitating ECM hydrogel formation without a disruptive enzymatic digestion process. Additionally, engineered hydrogels can contain more than one type of ECM (from bone, fat, liver, lung, spleen, cartilage, or brain), at various concentrations. These hydrogels demonstrated tunable gelation kinetics and mechanical properties, offering the possibility of numerous in vivo and in vitro applications with different property requirements. Retained bioactivity of ECM particles crosslinked into this hydrogel platform was confirmed by the variable response of stem cells to different types of ECM particles with respect to osteogenic differentiation in vitro, and bone regeneration in vivo . © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 147–159, 2018.